Preparation method of polyvinylidene fluoride ferroelectric layer coated carbon fiber super oil-absorbing material
Patent Information
- Application Number
- CN202410364923.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-03-28
AI Technical Summary
[0005]本发明的目的在于提供聚偏二氟乙烯铁电层包覆的碳纤维超吸油材料的制备方法,解决现有吸油材料油水分离效率低且稳定性差的问题
[0017](1)本发明的聚偏二氟乙烯铁电层包覆的碳纤维超吸油材料,采用紫外辐照辅助低温热处理技术,既实现了PVDF非铁电向铁电的转变,同时也实现了具有铁电性质的PVDF层与碳纤维的紧密结合;
Smart Images

Figure CN118147921B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of oil-absorbing material preparation technology, specifically relating to a method for preparing a carbon fiber super-oil-absorbing material coated with a polyvinylidene fluoride ferroelectric layer. Background Technology
[0002] Rapid purification and oil-water separation of wastewater containing oily organic matter has always been an urgent problem to be solved.
[0003] Oil-water separation materials refer to powdered, fibrous, gel-like, or aggregated materials capable of selectively adsorbing large quantities of oil stains and contaminants from water surfaces and recovering spilled oil. An ideal adsorbent material should possess hydrophobicity and oleophilicity, high oil absorption capacity, and low manufacturing cost. A common approach is to create various biomimetic surfaces with superhydrophobicity and oleophilicity through surface roughening and the introduction of low surface energy materials, thereby achieving high oil / water separation efficiency (>95%).
[0004] Carbon fiber is non-toxic and harmless, possesses a large number of microporous structures and a high specific surface area, exhibits high structural stability, is not easily corroded or deformed, and can maintain its adsorption properties and remain stable for a long time, making it widely used in oil-absorbing materials. However, oil-water mixtures contain a large number of impurities. After a period of use, traditional oil-water separation materials suffer from impurity deposition on the material surface, causing the functional coating to be covered by deposits and become ineffective. Since these deposits are difficult to degrade and eliminate, oil-water separation materials are not reusable, significantly increasing material usage costs. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing a carbon fiber super oil-absorbing material coated with a polyvinylidene fluoride ferroelectric layer, thereby solving the problems of low oil-water separation efficiency and poor stability of existing oil-absorbing materials.
[0006] The technical solution adopted in this invention is a method for preparing a carbon fiber super-oil-absorbing material coated with a polyvinylidene fluoride ferroelectric layer, which is implemented according to the following steps:
[0007] Step 1: Impregnate the carbon fiber in PVDF sol, remove it, and dry it to obtain carbon fiber with a PVDF layer coating;
[0008] Step 2: The carbon fiber with PVDF layer coating obtained in Step 1 is subjected to ultraviolet irradiation-assisted low-temperature heat treatment to obtain carbon fiber with PVDF layer coating that has ferroelectric properties.
[0009] Step 3: Immerse the PVDF-coated carbon fiber with ferroelectric properties obtained in Step 2 in a low surface energy modifier solution for modification, remove it, wash it with anhydrous ethanol, and dry it to obtain a polyvinylidene fluoride ferroelectric layer-coated carbon fiber super oil-absorbing material.
[0010] The invention is further characterized in that,
[0011] In step 1, the soaking time is 30 seconds, the drying temperature is 25-120℃, and the drying time is 0.5-2 hours.
[0012] In step 1, the preparation process of PVDF sol is as follows: PVDF powder is dissolved in polar DMF, and ultrasonic vibration or magnetic stirring is performed at 60-80℃ until PVDF is completely dissolved to obtain PVDF sol; the concentration of PVDF sol is 5-10 g / mL.
[0013] In step 2, during ultraviolet irradiation-assisted low-temperature heat treatment: the ultraviolet wavelength is 180–265 nm, the irradiation time is 0.5–2.5 h, and the heat treatment temperature is 100–200 °C.
[0014] In step 3, the concentration of the low surface energy modifier solution is 5–50 g / L; the low surface energy modifier solution is composed of a low surface energy modifier and anhydrous ethanol.
[0015] The low surface energy modifier is any one of octadecyltriethoxysilane, methoxytrimethoxysilane, aminopropyltriethoxysilane, and vinyltriethoxysilane.
[0016] The beneficial effects of this invention are:
[0017] (1) The carbon fiber super oil-absorbing material coated with polyvinylidene fluoride ferroelectric layer of the present invention adopts ultraviolet irradiation-assisted low temperature heat treatment technology, which realizes the transformation of PVDF from non-ferroelectric to ferroelectric, and also realizes the tight bonding between the PVDF layer with ferroelectric properties and carbon fiber.
[0018] (2) The carbon fiber super oil-absorbing material coated with polyvinylidene fluoride ferroelectric layer of the present invention has stable chemical properties of the ferroelectric PVDF layer coated on the surface of carbon fiber, thereby giving the carbon fiber oil-absorbing material excellent resistance to acid, alkali, salt and organic solvent.
[0019] (3) The polyvinylidene fluoride ferroelectric layer coated carbon fiber super oil-absorbing material of the present invention has a ferroelectric PVDF layer on the surface of the carbon fiber, which can impart a piezoelectric effect to the oil-absorbing material. By utilizing the energy generated by external mechanical pressure or strain, the deformation and surface charge distribution of the material can be controlled in real time. On the one hand, the water-oil separation process can be controlled in real time, improving the efficiency and selectivity of water-oil separation; on the other hand, the piezoelectric PVDF can also realize the repeated regeneration of the material, degrade and eliminate the precipitates adsorbed on the surface of the material, and restore its oil-water separation characteristics.
[0020] (4) The carbon fiber super oil-absorbing material coated with polyvinylidene fluoride ferroelectric layer of the present invention has a fluffy structure. Depending on the viscosity of different oils, the oil absorption ratio and oil retention rate can be guaranteed by adjusting the compaction density of the carbon fiber oil-absorbing material. Attached Figure Description
[0021] Figure 1 This is the hysteresis loop diagram of the carbon fiber oil-absorbing material containing a PVDF layer in Comparative Example 2.
[0022] Figure 2 This is a hysteresis loop diagram of the carbon fiber super-oil-absorbing material coated with a polyvinylidene fluoride ferroelectric layer prepared in Example 1.
[0023] Figure 3 This is a TEM image of the carbon fiber oil-absorbing material in Comparative Example 1;
[0024] Figure 4 This is a graph showing the relationship between the electric displacement of the material in Example 2 and voltage.
[0025] Figure 5 This is a graph showing the relationship between the phase of the material in Example 2 and voltage. Detailed Implementation
[0026] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0027] The preparation method of the carbon fiber super oil-absorbing material coated with a polyvinylidene fluoride ferroelectric layer of the present invention is carried out according to the following steps:
[0028] Step 1: Impregnate the carbon fiber in PVDF sol, remove it, and dry it to obtain carbon fiber with a PVDF layer coating;
[0029] The soaking time is 30 seconds, the drying temperature is 25-120℃, and the drying time is 0.5-2 hours.
[0030] The preparation process of PVDF sol is as follows: PVDF powder is dissolved in a polar N,N-dimethylformamide (DMF) organic solvent, and ultrasonically vibrated or magnetically stirred at 60-80℃ until PVDF is completely dissolved to obtain PVDF sol; the concentration of PVDF sol is 5-10 g / mL.
[0031] Step 2: The carbon fiber with PVDF layer coating obtained in Step 1 is transformed into carbon fiber with PVDF layer coating that has ferroelectric properties through ultraviolet irradiation-assisted low-temperature heat treatment.
[0032] When ultraviolet irradiation is used to assist low-temperature heat treatment: the ultraviolet wavelength is 180-265nm, the irradiation time is 0.5-2.5h, and the heat treatment temperature is 100-200℃.
[0033] Step 3: Immerse the PVDF-coated carbon fiber with ferroelectric properties obtained in Step 2 in a low surface energy modifier solution for 20 minutes, remove it, wash it with anhydrous ethanol to remove the residual modifier on the surface, and dry it to obtain PVDF-coated carbon fiber oil-absorbing material with ferroelectric properties (polyvinylidene fluoride ferroelectric layer-coated carbon fiber super oil-absorbing material).
[0034] The concentration of the low surface energy modifier solution is 5–50 g / L;
[0035] The low surface energy modifier solution is a mixture of a low surface energy modifier and anhydrous ethanol.
[0036] The low surface energy modifier is any one of octadecyltriethoxysilane, methoxytrimethoxysilane, aminopropyltriethoxysilane, and vinyltriethoxysilane;
[0037] Low surface energy modifiers typically reduce the surface tension of carbon fiber materials, allowing water to form a larger contact angle on their surface, thus improving hydrophobicity and enhancing their ability to adsorb oils. This treatment method enables oil-absorbing carbon fibers to adsorb oils more efficiently and quickly, contributing to improved oil absorption.
[0038] Carbon fiber, with its loose, porous structure and resistance to corrosion and deformation, is widely used in oil-absorbing materials. However, oil-water mixtures contain numerous impurities. After a period of use, these impurities accumulate on the surface of traditional oil-water separation materials, causing the functional coating to become covered and ineffective. Since these deposits are difficult to degrade and eliminate, traditional oil-water separation materials are not reusable, significantly increasing their cost. To achieve controllable regeneration and selective oil adsorption of oil-absorbing materials, this invention employs ultraviolet irradiation-assisted low-temperature heat treatment technology to coat the carbon fiber surface with a ferroelectric PVDF layer. This ferroelectric PVDF layer imparts a piezoelectric effect to the oil-absorbing material. Using the energy generated by external mechanical pressure or strain, real-time control of material deformation and surface charge distribution is achieved. This allows for real-time control of the oil-water separation process, improving efficiency and selectivity. Furthermore, the piezoelectric PVDF layer enables repeated regeneration of the material, degrading and eliminating deposits adsorbed on the surface and restoring its oil-water separation properties.
[0039] Example 1
[0040] The preparation method of the carbon fiber super oil-absorbing material coated with a polyvinylidene fluoride ferroelectric layer of the present invention is carried out according to the following steps:
[0041] Step 1: Immerse the carbon fiber in PVDF sol for 30 seconds, remove it, and dry it at 25°C for 2 hours to obtain carbon fiber with PVDF layer coating.
[0042] The preparation process of PVDF sol is as follows: PVDF powder is dissolved in DMF, magnetically stirred at 60℃ until PVDF is completely dissolved; the concentration of PVDF sol is 5g / mL.
[0043] Step 2: The carbon fiber with PVDF layer coating obtained in Step 1 is transformed into carbon fiber with PVDF layer coating that has ferroelectric properties through ultraviolet irradiation-assisted low-temperature heat treatment.
[0044] Among them, the ultraviolet wavelength of the ultraviolet light used in the ultraviolet irradiation-assisted low-temperature heat treatment was 180nm, the irradiation time was 100min, and the auxiliary heating temperature was 110℃.
[0045] Step 3: Immerse the PVDF-coated carbon fiber with ferroelectric properties obtained in Step 2 in a low surface energy modifier solution for modification, remove it, wash it with anhydrous ethanol to remove the residual modifier on the surface, and dry it to obtain PVDF-coated carbon fiber oil-absorbing material with ferroelectric properties.
[0046] The low surface energy modifier is octadecyltriethoxysilane with a concentration of 10 g / L; the solvent is anhydrous ethanol.
[0047] Example 2
[0048] The preparation method of the carbon fiber super oil-absorbing material coated with a polyvinylidene fluoride ferroelectric layer of the present invention is carried out according to the following steps:
[0049] Step 1: Immerse the carbon fiber in PVDF sol for 30 seconds, remove it, and dry it at 50°C for 1 hour to obtain carbon fiber with PVDF layer coating.
[0050] The preparation process of PVDF sol is as follows: PVDF powder is dissolved in DMF, magnetically stirred, and kept at 60℃ until PVDF is completely dissolved; the concentration of PVDF sol is 8g / mL.
[0051] Step 2: The carbon fiber with PVDF layer coating obtained in Step 1 is transformed into carbon fiber with PVDF layer coating that has ferroelectric properties through ultraviolet irradiation-assisted low-temperature heat treatment.
[0052] Among them, the ultraviolet wavelength of the ultraviolet light used in the ultraviolet irradiation-assisted low-temperature heat treatment was 200nm, the irradiation time was 150min, and the auxiliary heating temperature was 130℃.
[0053] Step 3: Immerse the PVDF-coated carbon fiber with ferroelectric properties obtained in Step 2 in a low surface energy modifier solution for modification, take it out, wash it with anhydrous ethanol to remove the residual modifier on the surface, and dry it at 40°C to obtain PVDF-coated carbon fiber oil-absorbing material with ferroelectric properties.
[0054] The low surface energy modifier is methoxytrimethoxysilane with a concentration of 15 g / L; the solvent is anhydrous ethanol.
[0055] Example 3
[0056] The preparation method of the carbon fiber super oil-absorbing material coated with a polyvinylidene fluoride ferroelectric layer of the present invention is carried out according to the following steps:
[0057] Step 1: Immerse the carbon fiber in PVDF sol for 30 seconds, remove it, and dry it at 120℃ for 0.5 hours to obtain carbon fiber with PVDF layer coating.
[0058] The preparation process of PVDF sol is as follows: PVDF powder is dissolved in DMF, magnetically stirred, and kept at 60℃ until PVDF is completely dissolved; the concentration of PVDF sol is 10g / mL.
[0059] Step 2: The carbon fiber with PVDF layer coating obtained in Step 1 is transformed into carbon fiber with PVDF layer coating that has ferroelectric properties through ultraviolet irradiation-assisted low-temperature heat treatment.
[0060] Among them, the ultraviolet wavelength of the ultraviolet light used in the ultraviolet irradiation-assisted low-temperature heat treatment was 237nm, the irradiation time was 120min, and the auxiliary heating temperature was 165℃.
[0061] Step 3: Immerse the PVDF-coated carbon fiber with ferroelectric properties obtained in Step 2 in a low surface energy modifier solution for modification, take it out, wash it with anhydrous ethanol to remove the residual modifier on the surface, and dry it at 40°C to obtain PVDF-coated carbon fiber oil-absorbing material with ferroelectric properties.
[0062] The low surface energy modifier is octadecyltriethoxysilane with a concentration of 10 g / L; the solvent is anhydrous ethanol.
[0063] Comparative Example 1
[0064] Preparation method of carbon fiber oil-absorbing material: carbon fiber is immersed in a low surface energy modifier solution for modification, taken out, washed with anhydrous ethanol to remove residual modifier on the surface, and dried at 40℃ to obtain carbon fiber oil-absorbing material;
[0065] The low surface energy modifier is octadecyltriethoxysilane with a concentration of 10 g / L; the solvent is anhydrous ethanol.
[0066] Comparative Example 2
[0067] Preparation method of carbon fiber oil-absorbing material containing PVDF layer: Immerse carbon fiber in PVDF sol for 30s, take it out, and dry it at 120℃ for 1h to obtain carbon fiber with PVDF layer coating.
[0068] The preparation process of PVDF sol is as follows: PVDF powder is dissolved in DMF, magnetically stirred, and kept at 60℃ until PVDF is completely dissolved; the concentration of PVDF sol is 5g / mL.
[0069] The carbon fibers with PVDF layer coating were immersed in a low surface energy modifier solution for modification. They were then removed, washed with anhydrous ethanol to remove the residual modifier on the surface, and dried at 40°C to obtain carbon fiber oil-absorbing material containing PVDF layer.
[0070] The low surface energy modifier is methoxytrimethoxysilane with a concentration of 10 g / L; the solvent is anhydrous ethanol.
[0071] The ferroelectric properties of the PVDF layers in the samples prepared in Example 1 and Comparative Example 2 were tested using a P-PMF ferroelectric workstation (manufacturer: Radiant Technologies). Figure 1 and Figure 2 As shown, PVDF without light irradiation exhibits obvious leakage current, while after light irradiation, it exhibits typical ferroelectric characteristics, indicating that ultraviolet light irradiation can promote the transformation of PVDF from non-ferroelectric to ferroelectric. PVDF is a material with multiple crystalline phases (α phase is paraelectric, β phase is ferroelectric) and also has certain photosensitivity properties. That is, under light irradiation of a specific wavelength, such as ultraviolet light, which is a high-energy light, it can excite electronic transitions in PVDF molecules, causing local structural changes in the PVDF molecular chain, such as changes in the orientation of chain segments and lattice arrangement, leading to changes in molecular structure, and thus causing the PVDF as a whole to undergo a ferroelectric transformation from the α phase to the β phase. Figure 3 The microstructure of individual carbon fibers after surface modification is shown; the addition of surfactants did not change their morphology.
[0072] The piezoelectric properties of the material in Example 2 were tested using an MFP-3D piezoelectric microscope (manufacturer: Asylum Research). Figure 4 and Figure 5 As shown, the typical butterfly curve and 180-degree domain transition indicate that the PVDF-coated carbon fiber oil-absorbing material has a piezoelectric effect. Under the action of eddy current or vibration, the oil-absorbing material can be regenerated. At the same time, it shows excellent separation performance for both gasoline / pure water and dichloromethane / pure water mixtures, with oil-water separation efficiencies of 96.5% and 97.4%, respectively.
Claims
1. A method for preparing a carbon fiber super-oil-absorbing material coated with a polyvinylidene fluoride ferroelectric layer, characterized in that, The specific steps are as follows: Step 1: Impregnate the carbon fiber in PVDF sol, remove it, and dry it to obtain carbon fiber with a PVDF layer coating; The preparation process of PVDF sol is as follows: PVDF powder is dissolved in polar DMF, and ultrasonic vibration or magnetic stirring is performed at 60-80℃ until PVDF is completely dissolved to obtain PVDF sol; Step 2: The carbon fiber with PVDF layer coating obtained in Step 1 is subjected to ultraviolet irradiation-assisted low-temperature heat treatment to obtain carbon fiber with PVDF layer coating that has ferroelectric properties. When ultraviolet irradiation is used to assist low-temperature heat treatment: the ultraviolet wavelength is 180-265nm, the irradiation time is 0.5-2.5h, and the heat treatment temperature is 100-200℃. Step 3: Immerse the PVDF-coated carbon fiber with ferroelectric properties obtained in Step 2 in a low surface energy modifier solution for modification, take it out, wash it with anhydrous ethanol, and dry it to obtain a polyvinylidene fluoride ferroelectric layer-coated carbon fiber super oil-absorbing material. The concentration of the low surface energy modifier solution is 5–50 g / L; the low surface energy modifier solution is composed of a low surface energy modifier and anhydrous ethanol; the low surface energy modifier is any one of octadecyltriethoxysilane, methoxytrimethoxysilane, aminopropyltriethoxysilane, and vinyltriethoxysilane.
2. The method for preparing the polyvinylidene fluoride ferroelectric layer-coated carbon fiber super-oil-absorbing material according to claim 1, characterized in that, In step 1, the soaking time is 30 seconds, the drying temperature is 25~120℃, and the drying time is 0.5~2 hours.
Citation Information
Patent Citations
Three-dimensional oil-water separating material based on static spinning technology and preparation method thereof
CN104674384A
Method and device for deeply treating wastewater by coupling PVDF / ZnO piezoelectric ultrafiltration membrane to advanced oxidation technology
CN107739116A
Process for manufacturing a pyroelectric and / or piezoelectric drive
US20160276569A1
